The implementation of state's rights and obligations in outer space: is it equal? - Yusliwidaka, Arnanda; Roisah, Kholis; Setiyono, Joko (Faculty of Law, University of Muhammadiyah Malang, 2024)
The provisions of Outer Space Law govern a state's activities in outer space. The implementation of such activities needs advanced technology, which limits the ability of many countries to explore and exploit outer space. Data indicates that developed nations dominate outer space management, leaving countries without access to sophisticated technology unable to participate fully in space exploration and exploitation. This dominance triggers disparity between developed and developing countries, leading to unequal application of rights and obligations as outlined in Outer Space Law. While the law promotes international collaboration to address this issue, it does not explicitly require developed countries to involve developing nations in outer space activities. This study aims to refine the concept of international collaboration to ensure fair management and exploitation of outer space by all countries. This study is normative in nature, focusing on evolving the concept of international collaboration in outer space. Primary and secondary legal materials and non-legal sources were used as secondary data collected through a literature review and analysed qualitatively. The developed concept emphasises international cooperation and mutual assistance, proposing a framework for collaboration between developed and developing countries. This concept seeks to ensure equitable management of outer space. It reshapes the rights and obligations of states by encouraging all launching states to involve developing countries in space exploration and exploitation.